The Influence Of Product, Price, And Promotion On Customer Trust In The Thrifting Business In Tulungagung Outfit - Ilham Quddus Ramadani; Ahmad Syaichoni; Handri Handri (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
Public trust in the products offered at thrift shops is a challenge that must be faced by thrift shop businesses, and the low level of public trust cannot be blamed because judging from what is happening in the field, second-hand products are of unclear origin and cannot be separated. of the risks of its use. The research objectives include: (1) To determine and analyze the effect of product, price, and promotion together (simultaneously) on customer trust in the thrifting business in Tulungagung outfits. (2) To find out and analyze the influence of individual products (partial) on customer trust in the thrifting business in Tulungagung outfits. (3) To find out and analyze the effect of individual (partial) prices on customer trust in the thrifting business in Tulungagung outfits. (4) To find out and analyze the effect of individual (partial) promotions on customer trust in the thrifting business in Tulungagung outfits. (5) To find out and analyze the variables of product, price, and promotion that have a dominant influence on customer trust in the thrifting business in Tulungagung outfits. This study uses a quantitative approach, which is used to determine the effect of production, price, and promotion on customer trust in Outfit Tuulangagung. The analysis used is the data in the form of numbers. While the data analysis method used: (1) descriptive data analysis, (2) classical assumption test, (3) and inferential statistical analysis. The results showed that: (1) Product, price, and promotion simultaneously (simultaneously) had a significant effect on customer trust in the thrifting business in Tulungagung outfits. (2) Individual products (partial) have a significant effect on customer trust in the thrifting business in Tulungagung outfits. (3) The price individually (partial) has a significant effect on customer confidence in the thrifting business in Tulungagung outfits. (4) Individual promotion (partial) has a significant effect on customer confidence in the thrifting business in Tulungagung outfits. (5) Promotion has the most dominant effect on customer trust in the thrifting business in Tulungagung outfits.